Active Metal Catalysts: Phase Coexistence and Structural Dynamics of Redox Metal Catalysts Revealed by Operando TEM (Adv. Mater. 31/2021). Issue 31 (4th August 2021) - Huang, Xing; Jones, Travis; Fedorov, Alexey; Farra, Ramzi; Copéret, Christophe; Schlögl, Robert; Willinger, Marc‐Georg
Abstract : The active state of heterogeneous catalysts is typically metastable and can only be generated under actual reaction conditions. In article number 2101772, Xing Huang, Marc‐Georg Willinger, and co‐workers report an operando transmission electron microscopy study to characterize chemical dynamics and surface sites of metal catalysts, as well as their correlations to catalytic activity under relevant redox reactions, providing new insights into the functioning state of active metal catalysts and underlining the importance of chemical dynamics for the formation and constant re‐generation of transient active sites during catalysis.